Implementing Job Safety Analysis to Analyze Hazard Risk Factors for Paper Core Workers - Saputra, Dwi Arwandi Yogi; Savitri, Pritha Maya; Perdini, Fitriana Titis; Harjono, Yanti; Lestari, Muhammad Mansyah; Abqo, Toriq; Monica, Vira; Maulidawati, Alma Putri; Kusumahdipura, Rayhan Fawzy; Gading, Massayu Savira (Academia Open, 2026)
General Background: Occupational safety and health remain critical concerns in industrial manufacturing due to persistent exposure to physical, chemical, and ergonomic hazards. Specific Background: Paper core manufacturing involves high-speed machinery, heavy material handling, elevated temperatures, and continuous noise, which collectively pose risks for work-related diseases. Knowledge Gap: Despite routine production activities, systematic identification and prioritization of occupational health risks in paper core factories using structured analytical methods remain limited. Aims: This study aimed to identify and assess occupational safety and health hazards among paper core workers using the Job Safety Analysis approach. Results: The analysis identified noise and high temperature exposure as high-risk hazards, particularly associated with winding, cutting, trimming, and seamless processes, with hypertension emerging as a prominent occupational health risk among workers exposed for eight-hour shifts. Other hazards, including dust exposure, ergonomic strain, and chemical contact, were categorized as medium to low risk. Novelty: This study provides a comprehensive, process-based hazard mapping of paper core manufacturing activities using Job Safety Analysis, explicitly linking high-risk operational stages with hypertension risk classification. Implications: The findings support the need for structured risk assessments, environmental controls, ergonomic interventions, and continuous health monitoring to manage occupational health risks and support worker safety and productivity in paper core manufacturing facilities. Highlights: High-temperature and acoustic conditions were classified as dominant high-risk hazards across multiple production stages. Cardiovascular conditions were identified among workers subjected to prolonged industrial exposure. Structured hazard mapping enabled prioritization of preventive workplace controls. Keywords: Job Safety Analysis, Ergonomics, Health, Safety